2020
DOI: 10.1002/brb3.1587
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of SynCAM1/CADM1 PDZ interactions with MUPP1 using mammalian and bacterial pull‐down systems

Abstract: Background: Synaptic cell adhesion molecule 1 (SynCAM1) also known as cell adhesion molecule 1 (CADM1) is a transmembrane cell adhesion protein that operates in a variety of physiological and pathological cellular contexts, and its interaction with the PDZ signalling protein MUPP1 have been previously implicated in autism spectrum disorder (ASD). Methods:We used in vitro pull-down systems based on the bacterial and mammalian extracts to study SynCAM1/CADM1 PDZ interactions with MUPP1 at various conditions.Resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…In subsequent work, we decided to investigate the interactions of PDZ peptide motifs of coronaviruses with MUPP1 homologue PATJ/INAD [ 32 ], which is similar to MUPP1 associated with epithelial tight junctions through its non PDZ interaction with PALS1 [ 33 ]. Similar to MUPP1, PATJ interacted with SARS-CoV and SARS-CoV2 PDZ motif mainly through PDZ domains 2 and 3, and domain 9, which is the homologue of MUPP1 domain 11 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In subsequent work, we decided to investigate the interactions of PDZ peptide motifs of coronaviruses with MUPP1 homologue PATJ/INAD [ 32 ], which is similar to MUPP1 associated with epithelial tight junctions through its non PDZ interaction with PALS1 [ 33 ]. Similar to MUPP1, PATJ interacted with SARS-CoV and SARS-CoV2 PDZ motif mainly through PDZ domains 2 and 3, and domain 9, which is the homologue of MUPP1 domain 11 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this article, we probed MUPP1 also named MPDZ protein [ 31 ] and its homologue PATJ/INAD [ 32 , 33 ] for their potential PDZ interactivity with the SARS-CoV, SARS-CoV2, and MERS-CoV protein E PDZmotifs. Our previous results showed that a core PDZ motif interactivity is relatively promiscuous, suggesting that in vivo might be switched on/off by so far unidentified allosteric structural changes of protein complexes [ 34 ].…”
Section: Introductionmentioning
confidence: 99%